THE CORRELATION OF STUDENTS INTEREST TO CHARACTER AND THEIR ACHIEVEMENT ON ATOMIC STRUCTURE TOPIC - Yohanita Nirmalasari (Universitas Negeri Surabaya, 2020)
This research aims to know 1) students interest, 2) discipline character, 3) students achievement, 4) correlation between students interest to discipline character and their achievement on atomic structure topic. Sample research were 20 students from class A of SMAK St. Petrus Kewapante which is collected randomly. Teaching method used cooperative learning type number head together (NHT). The technique of data collection was essay test, questionnaires and observation, which analyzed by descriptive quantitative and multiple linear regression. The result showed 1) based on teacher observation data indicated students interest as best category (90%) and good category (10). 2) students disciplinary as best category (80%) and good category (20%), while 100% as best category based on teachers observation data. 3) students achievements result showed average value in 51,75 and 80,50 as pre-test and post-test result respectively. 4) there is no correlation between students interesting to disciplinary character and their achievements in learning chemistry.